تأثير طرائق الحراثة في الكثافة الفعلية لنبات الفول، ونسبة الجذور، وبعض الدلائل الإنتاجية - عبد العزيز محمد; نقولا ميشيل (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث خلال الموسمين الزراعيين 2009 ـ 2010 في منطقة القصير جنوب غرب مدينة حمص، لدراسة تأثير طرائق الحراثة في الكثافة النباتية الفعلية للنباتات، والنسبة بين المجموع الخضري والجذري، ودليل المساحة الورقية، وبعض الدلائل الإنتاجية (دليل الحصاد، دليل المحصول، القوة النسبية للبذور). استخدم لذلك أربع طرائق للحراثة، هي: 1 ـ حراثة سطحية (T1)، 2 ـ حراثة مطرحية (T2)، 3 ـ حراثة قرصية (T3)، 4 ـ حراثة شاقة (T4). صممت التجربة بطريقة القطاعات العشوائية الكاملة في خمسة مكررات. فبينت الدراسة النتائج الآتية: * تفوقت طرائق الحراثة المطرحية (T2)، والقرصية (T3)، والشاقة (T4) معنوياً على الحراثة السطحية (T1) في الكثافة الفعلية، والنسبة بن المجموع الجذري والخضري، ودليل المساحة الورقية، ودليل الحصاد، ودليل المحصول، والقوة النسبية للبذور. * تفوقت الحراثة الشاقة (T4) معنوياً على طريقتي الحراثة المطرحية (T2)، والقرصية (T3) في المؤشرات كافة المذكورة أعلاه، وبالمقابل لم توجد فروق معنوية بين الحراثة المطرحية (T2)، والحراثة القرصية (T3) في جميع المؤشرات التي تم دراستها باستثناء دليل المساحة الورقية في الموسم الثاني فقط. The research was carried out during 2009-2010 in agricultural seasons, in Alqusser area, western south of Homs city to study the effect of ploughing methods on actual plant density (FPD), Root/Shoot Ratio(RSR), Leaf Area Index (LAI), and some yield indications, Harvest Index (HI), Crop Index(CI), and Relative Seeds Strength (RSS). Using (4) ploughing methods, (surface tillage (T1), disk tillage (T2), place tillage (T3), and disk-turning (T4). Arandomezd black design, with (5) replicqtions, the study showed the following: A significat increase in ploughing methods (disk-tillage (T2). place tillage (T3), and disk-turning (T4) over surface tillage in actual plant density, root/Shoot Ratio, leaf Area index, Harvis Index, Crop Index, and Relative Seeds Strength on surface tillage (T1). A significant increase in disk-turning (T4) on ploughing methods, disk-tillage (T2), and place tillage (T3) in all indicators mentioned above. On the other hand there was no significant increase between ploughing method disk- tillage and place tillage in all study indicationsexcept leaf area index only during the second season.